FRAMBOIDAL PYRITES IN LATE QUATERNARY CORE SEDIMENTS OF THE EAST SEA AND THEIR PALEOENVIRONMENTAL IMPLICATIONS - Park M.-H.; Kim I.-S.; Ryu B.-J. (My University, 2003)
The three piston cores, collected from the East Sea, were analyzed to detect changes of sedimentary environment during the late Quaternary. The cores consist mainly of muddy sediments that are interbedded with silty sands, lapilli and ash layers. The so-called dark laminated mud (DLM) layers are found during the last-glacial and interglacial transition. The geochemical results document that the DLM layers are enriched in Fe relative to Mn. Fe is present as a form of framboidal pyrite, which shows a proportion of about 2∶1 for S and Fe. Based on the morphology, the pyrites are regarded to have grown in the transitional state between high and low supersaturations of Fe and S. Furthermore, the framboidal size distribution implies that the DLM layers have deposited in euxinic environments.
Keywords: framboidal pyrite; dark laminated mud; euxinic; late Quaternary; East Sea; Cenozoic::Quaternary; Кайнозой::Четвертичная